Address Presenting the Third Annual Report - McCloy, John J. (World Bank, Washington, DC, 2019)
John J. McCloy, President of the International Bank for Reconstruction and Development, discussed the European Recovery Program and the role of Bank in it. He reported on provisions for using loan proceeds. He was proud of a guarantee operation to sell the notes of Dutch shipping companies to U.S. banks. He spoke about how the Bank sold to the Bank for International Settlements an issue of Swiss Franc bonds, and the proceeds were used in the loan to The Netherlands. He concluded by talking about variety of the projects presented to the Bank from all over the world and how this would keep the Bank busy.